Ultrahigh molecular weight polyethylene: catalysis, structure, properties, processing and applications - Patel, Ketan; Chikkali, Samir H.; Sivaram, Swaminathan (Progress in Polymer Science, 2020)
Ultrahigh molecular weight polyethylene (UHMWPE) belongs to an emerging class of high-performance specialty polymers with a unique set of properties and applications. The field has witnessed many scientific and technological advances in recent years. However, synthesis of UHMWPE is not a trivial exercise and presents several challenges. This review addresses these fundamental challenges and provides an overview of recent developments in the field of UHMWPE. The nature of catalysts, reaction conditions that favor its formation, their physical properties, methods of processing them into products, and their applications are discussed. Recent developments in formation of UHMWPE in a disentangled state by use of appropriate catalysts and reaction conditions are also discussed. This has elicited considerable interest as a means of enabling melt processing of UHMWPE. This review provides a comprehensive source of information and understanding of the multifaceted aspects of UHMWPE with specific reference to chemistry, catalysis, processes for manufacturing, and an analysis of catalyst structure-polymer property relationships. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Catalysts for UHMWPE; Disentangled UHMWPE; Entangled UHMWPE; polyethylene (PE); Ultrahigh molecular weight (UHMW) PE